2003
DOI: 10.1002/elps.200390128
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation of 3,4‐methylenedioxymeth‐ amphetamine and related compounds in clandestine tablets and urine samples by capillary electrophoresis/fluorescence spectroscopy

Abstract: The R-(-)- and S-(+)-isomers of 3,4-methylenedioxymethamphetamine (MDMA) and its metabolite 3,4-methylenedioxyamphetamine (MDA) were prepared, identified by gas chromatography/mass spectrometry (GC/MS) and then used as standards in a series of capillary electrophoresis (CE) experiments. Using these R-(-)- and S-(+)-isomers, the distribution of (RS)-MDA and (RS)-MDMA stereoisomers in clandestine tablets and suspect urine samples were identified. Several electrophoretic parameters, such as the concentration of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Urea has been applied to increase the solubility of a CD; it has also been used as an organic modifier, 31 and recently for the chiral separation of methamphetamine derivatives. 32 As can be seen from Fig. 2(b), TIQ, DA, (R/S)-Sal, (R)-NMSal and (R/S)-BTIQ were well separated using a running buffer consisting of 1.5 M urea, 12 mM β-CD, and 50 mM phosphate (pH 3.0).…”
Section: Separation Of Tetrahydroisoquinoline (Tiq) Derivativesmentioning
confidence: 82%
“…Urea has been applied to increase the solubility of a CD; it has also been used as an organic modifier, 31 and recently for the chiral separation of methamphetamine derivatives. 32 As can be seen from Fig. 2(b), TIQ, DA, (R/S)-Sal, (R)-NMSal and (R/S)-BTIQ were well separated using a running buffer consisting of 1.5 M urea, 12 mM β-CD, and 50 mM phosphate (pH 3.0).…”
Section: Separation Of Tetrahydroisoquinoline (Tiq) Derivativesmentioning
confidence: 82%
“…Since both methods were validated, either of them may be considered for routine analysis of diazepam in a clinical laboratory. Huhn et al [198] recently developed a CE [194] with permission. method combined with UV-LIF detection for the analysis of tryptamine derivatives which can be found in synthetic illicit drugs of abuse.…”
Section: Forensic Applicationsmentioning
confidence: 98%
“…Bokor et al [193] reported on the development of a validated CZE method using citrate/ phosphate, pH 2.5 with added hydroxypropyl-b-CD for the analysis of the optical isomers of methamphetamine. More recently, Huang et al [194] used b-CD dissolved in a mixture of methanol-ACN-water, 3 M urea, phosphate buffer, pH 3.0 to separate the enantiomers of methamphetamine and its metabolites. Importantly they were showed that the method would work using urine from people suspected of injesting methamphetamine (Fig.…”
Section: Forensic Applicationsmentioning
confidence: 99%
“…In addition, a high sensitivity cell was used for the enantioselective analysis of fluoxetine and norfluoxetine in plasma samples by CEC, using vancomycin as stationary phase [133]. Conventional fluorescence detection has been employed for the analysis of 3,4-methylenedioxymethamphetamine and related compounds in urine samples [57] and albendazole sulfoxide in plasma and saliva samples [69]. Even though a more sensitive detector was used, the quantification limit obtained by Prost et al [69] was identical to the quantification limit obtained by UV detection [67], i.e., 0.1 mg/mL.…”
Section: Sensitivity and Detectionmentioning
confidence: 99%
“…In addition to the substituent group, the mean number of derivatized hydroxyls in the CD molecule (the degree of substitution, d.s., defined as the number of functionalyzed groups per torus) [22] is also important for chiral resolution. As shown in Table 1, 2-hydroxypropyl-b-cyclodextrin (HP-b-CD) was the most frequently used neutral CD derivative (57%), followed by a-CD (22%), b-CD (7%), heptakis-2,6-di-Omethyl-b-cyclodextrin (DM-b-CD, 7%), and heptakis-2,3,6-tri-O-methyl-b-cyclodextrin (TM-b-CD, 7%) [44][45][46][47][48][49][50][51][52][53][54][55][56][57]. LLE, liquid-liquid extraction; LPME, liquid-phase microextraction; MDA, 3,4-methylenedioxyamphetamine; PP, protein pre-…”
Section: Separation Modes and Chiral Selectorsmentioning
confidence: 99%